Microbubble contrast agents for medical ultrasound imaging: Current issues and new directions - Eckersley, R; Chetty, K; Stride, E; Tang, M (2008)
Microbubbles have shown great promise for enhancing medical ultrasound imaging, with both potential and proven applications in Radiology and Cardiology and many other clinical areas. More recently the use of targeted agents for molecular imaging is being studied and the use of microbubble as mediators for the delivery of drugs and gene therapy is being investigated. In this presentation the basis for these different uses of microbubbles will be described and the challenges which are limiting the widespread acceptance and implementation of these techniques, will be outlined. These include issues relating to image artefacts, image quantitation and the complexity of interactions between microbubbles and both the ultrasound field and the human body.